The Relationship of Reproductive Health Education from Teachers and Parents with Adolescents' Attitudes to Free Sex at SMA Negeri 1 Tapa - Ramdan Usulu; Ridha Hafid; Sartika (Universitas Muhammadiyah Palu, 2026)
Adolescence is a developmental stage characterized by rapid physical, psychological, and social changes, making adolescents more vulnerable to engaging in risky sexual behaviors. Reproductive health education provided by teachers and parents plays a crucial role in shaping adolescents' attitudes toward free sex. However, limited communication and comprehensive education may increase the risk of unhealthy sexual behaviors. This study aimed to analyze the relationship between reproductive health education provided by teachers and parents and adolescents' attitudes toward free sex at SMA Negeri 1 Tapa. This quantitative analytical study employed a cross-sectional design. The study population consisted of 478 students, with 83 respondents selected using proportionate stratified random sampling. Data were collected using structured questionnaires and analyzed through univariate analysis and Spearman Rank correlation with a significance level of 5% (? = 0.05). Most respondents received reproductive health education from teachers at a moderate level (56.7%) and from parents at a high level (73.5%). Adolescents' attitudes toward free sex were predominantly in the moderate category (51.8%). The findings revealed a significant relationship between reproductive health education provided by teachers and adolescents' attitudes toward free sex (p = 0.022; r = -0.252). Likewise, a significant relationship was found between reproductive health education provided by parents and adolescents' attitudes toward free sex (p = 0.022; r = -0.252). The correlation coefficients indicated a weak negative relationship, suggesting that better reproductive health education was associated with more positive attitudes in rejecting free-sex behavior. Reproductive health education provided by teachers and parents is significantly associated with adolescents' attitudes toward free sex. Strengthening collaboration between schools and families through continuous, comprehensive, and age-appropriate reproductive health education is essential to foster responsible attitudes toward reproductive health among adolescents.